Harnessing the Power of Optical Microscopic and Macroscopic Imaging for Natural Products as Cancer Therapeutics - Yan, Tianyu; Zeng, Qi; Wang, Lin; Wang, Nan; Cao, Honghao; Xu, Xinyi; Chen, Xueli (Frontiers in Pharmacology, 2019)
Natural products (NPs) are an important source for new drug discovery over the past decades, which have been demonstrated to be effectively used in cancer prevention, treatment and adjuvant therapy. Many methods, such as the genomic and metabolomic approaches, immunochemistry, mass spectrometry, and chromatography, have been used to study the effects of NPs on cancer as well as themselves. Because of the advantages in specificity, sensitivity, high throughput, and cost-effectiveness, optical imaging (OI) approaches, including optical microscopic imaging and macroscopic imaging techniques have also been applied in the studies of NPs. Optical microscopic imaging can observe NPs as cancer therapeutics at the cellular level and analyze its cytotoxicity and mechanism of action. Optical macroscopic imaging observes the distribution, metabolic pathway, and target lesions of NPs in vivo, and evaluates NPs as cancer therapeutics at the whole-body level in small living animals. This review focuses on the recent advances in NPs as cancer therapeutics, with particular emphasis on the powerful use of optical microscopic and macroscopic imaging techniques, including the studies of observation of ingestion by cells, anticancer mechanism, and in vivo delivery. Finally, we prospect the wider application and future potential of OI approaches in NPs as cancer therapeutics.